Export Diversification and Economic Growth in Indonesia: An ARDL Model Analysis - Fadhlani, Muhammad Fauzan; Irawan, Tony; Priyarsono, Dominicus Savio (Jurnal Ekonomi Pembangunan, 2024)
The anomalies in Indonesia's export data underpin this research, which examines the patterns of export diversification in Indonesia and its impact on economic growth using the ARDL model. This study investigates export diversification and its effects on economic growth, considering variables such as gross fixed capital formation and labor. The data used spans the period from 1989 to 2022. This study is the first to consider Indonesia as a case study with valid pre-estimation testing. This study found that export diversification has a significant impact on economic growth in Indonesia and provides valuable insights into the relationship between export diversification and economic growth, highlighting policy implications to encourage diversification and mitigate risks associated with dependence on a few key markets. This study emphasizes the need for better diversification strategies to ensure economic stability and long-run growth.